2017
DOI: 10.7860/jcdr/2017/24172.9220
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Dyslipidemia in Patients with Chronic Kidney Diseases

Abstract: Introduction: Chronic Kidney Disease (CKD) is a major and globally increasing health problem in the general population arising from a spectrum of diseases. Majority of the patients die even before reaching End Stage Renal Disease (ESRD) due to cardiovascular complications which arise due to altered lipoprotein compositions.Aim: Present study was aimed at evaluating the serum lipid profile in CKD patients and to find the pattern of its alteration in both haemodialyzed and conservatively treated CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
4
0
2
Order By: Relevance
“…Regarding the lipid profile, the results obtained were compatible with a recent study which concluded that an elevation of triglycerides with a reduction in HDL-C, instead of an increase in total cholesterol and LDL, are responsible for the high incidence of cardiovascular complications in patients with CKD [32]. In addition, there was a significant correlation between total cholesterol and MPO parame-▶table 2 Biochemical and hematological parameters of the groups: control (CON), end-stage renal disease (ESRD) and end-stage renal disease with cardiovascular disease (ESRD/CVD).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the lipid profile, the results obtained were compatible with a recent study which concluded that an elevation of triglycerides with a reduction in HDL-C, instead of an increase in total cholesterol and LDL, are responsible for the high incidence of cardiovascular complications in patients with CKD [32]. In addition, there was a significant correlation between total cholesterol and MPO parame-▶table 2 Biochemical and hematological parameters of the groups: control (CON), end-stage renal disease (ESRD) and end-stage renal disease with cardiovascular disease (ESRD/CVD).…”
Section: Discussionsupporting
confidence: 89%
“…These observations are similar to study from north India which revealed that increased TG, increased VLDL-C and reduced HDL-C levels rather than increased TC and LDL-C levels are responsible for increased cardiovascular complications in CKD patients. 32 Ahmad et al in a study in 2018 observed increased TC,TG, LDL-C and VLDL-C and reduced HDL-C levels in CKD patients with and without hemodialysis as high risk for development of dyslipidemia as hemodialysis effectively reduces the nitrogenous waste products but fails to clear dyslipidemia. 33 In hemodialysis there is more oxidative stress leading to dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CKD show alterations in the serum lipid profile which differ from those in the general population. A recent study showed that, although the total cholesterol was low in patients with CKD, the triglyceride elevation, VLDL and HDL cholesterol decrease were responsible for cardiovascular events 10 .…”
Section: Lipid Intakementioning
confidence: 99%